Factorise:xy-ab+bx-ay Urgently need the answer​

Question

Factorise:xy-ab+bx-ay Urgently need the answer​

in progress 0
Alaia 1 month 2021-09-22T00:47:21+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-22T00:48:30+00:00

    Answer:

    we have

    xy-ab+bx-ay=xy-ay-ab+bx

    =y(x-a) -b(a-x) [the sign of -b(a-x) will change to make the brackets same, it become b(x-a)

    = y(x-a) +b(x-a)

    = (x-a) (y+b)

    so (x-a) (y+b) is the correct answer.

    please mark as brainliest

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )